First TSI results and status report of the CLARA/NorSat-1 solar absolute radiometer. Issue Volume 14:Issue A30(2018) (August 2018) - Walter, Benjamin; Andersen, Bo; Beattie, Alexander; Finsterle, Wolfgang; Kopp, Greg; Pfiffner, Daniel; Schmutz, Werner
Abstract: The Compact Lightweight Absolute Radiometer (CLARA) is orbiting Earth on-board the Norwegian NorSat-1 micro-satellite since 14 th of July 2017. The first light total solar irradiance (TSI) measurement result of CLARA is 1360.18 W m −2 for the so far single reliable Channel B. Channel A and C measured significantly lower (higher) TSI values and were found being sensitive to satellite pointing instabilities. These channels most likely suffer from electrical interference between satellite components and CLARA, an effect that is currently under investigation. Problems with the satellite attitude control currently inhibit stable pointing of CLARA to the Sun.